PRICE WAR: AN EMPIRICAL STUDY IN INDONESIAN MARKETPLACE - Muhammad Rheza Ramadhan (Jurnal Ekonomi dan Manajemen, 2022)
The goal of this research is to create a price war model for the Indonesian market and examine actual data from price competition in the country (Shopee Indonesia). According to the Bertrand basic model, if two sellers have similar cost structures and offer homogenous items, the seller must establish a price at marginal cost and cannot change it. The company will be unable to sell its own items if the price is raised. The Bertrand model for differentiated products then demonstrates that if the differentiated commodities are comparable, the price choice is influenced by the cost structure. If a company's cost structure is consistent, the price set will be consistent as well. Empirically, it is difficult to locate suppliers that match the Bertrand basic model's criteria, particularly when it comes to the same cost structure. However, empirical evidence shows that price wars occur in homogenous product marketplaces, even when prices are not same owing to cost structure variations. In a differentiated product market, on the other hand, the pattern of price fluctuations tends to vary from one another.